The Relationship Between the Healthy Diet Index, Chronic Diseases, Obesity and Lifestyle Risk Factors Among Adults in Kaunas City, Lithuania - Dėdelė, Audrius; Bartkutė, Žydrūnė; Chebotarova, Yevheniia; Miškinytė, Auksė (Frontiers in Nutrition, 2021)
A healthy and balanced diet is an important factor contributing to overall health and wellness. The aim of this study was to develop a Healthy Diet Index (HDI) score and assess its association with various chronic diseases and lifestyle risk factors. A cross-sectional survey included 1,111 adults aged 18 years and older. Information on dietary habits was collected using a questionnaire. Additional demographic, socioeconomic and lifestyle risk factors data were also collected. Sixteen food groups were used to develop the HDI score for the residents of Kaunas city, Lithuania based on the national recommendations, World Health Organization (WHO) and other guidance on a healthy diet. We used logistic regression models to assess the association of the HDI score with chronic diseases, obesity and lifestyle risk factors. We found that both males and females were lacking the optimal consumption of the base components of a healthy diet–fruits and vegetables, starchy carbohydrates, and proteins. We also observed significant associations between the HDI score and several outcomes such as hypertension, arrhythmia, physical activity, and obesity. The suggested HDI score could serve as a valuable tool in assessing and improving dietary habits beneficial for promoting health and preventing many diseases.